Age-specific benefits of Vitamin D and its association with mortality - Yan Wang; Xueqin Zhang; Xu Wang; Ju Li; Kai Wang (PLoS ONE, 2025)
Background Vitamin D is a fat-soluble secosteroid that plays essential roles in calcium homeostasis, bone metabolism, and numerous other physiological processes. Vitamin D deficiency has been associated with increased risk of various diseases and mortality. However, population-based studies examining the relationship between vitamin D and mortality across different age groups remain limited. Methods To investigate the correlation between 25-hydroxyvitamin D [25(OH)D] levels, vitamin D status, and mortality in a cohort of 47,478 individuals aged 18–85 years. Results Higher 25(OH)D levels were associated with lower mortality risk. Compared to the vitamin D deficiency group, the Hazard ratios (HR) for all-cause mortality were 0.71 (95%CI: 0.66–0.76) in the insufficiency group and 0.64 (95%CI: 0.58–0.70) in the sufficiency group. The association varied by age: strongest in adults aged 40–59 years (HR: 0.74, 95% CI: 0.65–0.85), significant in those ≥60 years (HR: 0.86, 95% CI: 0.82–0.90), but non-significant in those aged 18–39 years. The RCS analysis revealed a non-linear relationship between 25(OH)D and mortality, with significant risk reduction observed between 59.25–261.45 nmol/L for the overall population. The optimal 25(OH)D levels (lowest HR) varied by subgroups: 96.81 nmol/L for the overall population, 102.9 nmol/L for females, 67 nmol/L for ages 40–59, and 104.23 nmol/L for ages ≥60 years, while no significant association was found in ages 18–39 years. Conclusion Our findings suggest that Vitamin D are associated with mortality among the whole population. Individuals aged 40–59 may derive potential benefits from vitamin D supplementation.